FOOTPRINTS OF IRANIAN HERITAGE IN BALTISTAN, PAKISTAN: A CULTURAL PERSPECTIVE - Dr. Muhammad Safeer; Mr. Sajjad Hussain; Dr. Syeda Chand Bibi (International Journal of Contemporary Issues in Social Sciences, 2023)
The present study aims to explore the linguistic and cultural outcomes of the Persian influence on the cultural heritage of Pakistan, especially Baltistan. The Persian language, literature, and culture imperceptibly weaved into the linguistic and cultural spheres of Pakistan. However, the influence is more prominent and visible in the Baltistan region of the country where their language(s) and cultural heritage have heavily absorbed the Persian lexicon and cultural peculiarities that have entirely modified their perspective of the world. As the Persian preachers brought Islam to this region, the Persian cultural heritage was accompanied as a byproduct of the new religion. Beyond religious practices, Persian culture has crept into this society and Nowruz is one of the best examples of the Persian cultural infusion into the cultural traditions of this region. The locals celebrate this festival with religio-cultural fervor and have incorporated many exotic, i.e., Persian, and few local peculiarities into this event. The festivities of the Nowruz celebration range from decorating houses to egg tapping and then concluding the day with a polo match. Baltistan and its neighboring communities may never be able to cast off the spell of Persian language and culture upon their languages and cultural events that subtly intruded and settled into the linguistic and cultural heritage of this region.